PENGARUH TEKNIK REFRAMING UNTUK MENURUNKAN KECEMASAN BERBICARA DI DEPAN UMUM MELALUI BIMBINGAN KELOMPOK DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Ilyas, Elyawati; Rosmawati, Rosmawati; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of reframing techniques on reducing anxiety in public speaking of students in SMK Labor Binaan FKIP UNRI Pekanbaru. This type of research is quantitative research with experimental methods using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is a scale that measures students' public speaking anxiety consisting of 50 items before validation, and after validation 40 items are obtained with valid validity of 0.562 and reliability of 0.953. The subjects of this study were 8 students who were identified as having high levels of public speaking anxiety. The data analysis technique used is non-parametric statistical techniques using the Rank Spearman test. The research results prove the research hypothesis is accepted. For that from the Spearman Rank test results obtained r = 0.762 while the correlation coefficient r2 is 0.58. Thus there is the influence of cognitive restructuring techniques on student academic procrastination of 58% in the SMK Labor Binaan FKIP UNRI Pekanbaru. From the Wilcoxon test results obtained (Asymp.Sig) 0.012 <0.05, it can be concluded that there are differences in public speaking anxiety scores of students before and after reframing given treatment.Key Words: Reframing, Public Speaking Axiety